Tiktok New Media Analysis as Personal branding (Qualitative Description Study on Tiktok Account @Vmuliana) - Erfina Monica Putri; Poppy Febriana (Mahesa Research Center, 2023)
Along with the rapid development of technology and followed by the development of new media, it has its own influence on the creation of various sites interacting through the virtual world. Until then, a new communication medium was created, one of which was Tiktok. The new media Tiktok is a social media platform that uses short videos of about 15 seconds - 3 minutes accompanied by music. The presence of Tiktok has another function, with Tiktok also being able to build personal branding from its owner. A content creator, named Vina A. Muliana, is quite familiar to the ears. The content published through Tiktok is packaged by Vina in a unique and fun way. This study aims to find out how the new media Tiktok as a personal branding tool for Vina A. Muliana. The problem is focused on the personal branding of Vina A. Muliana, in order to approach this problem, the theoretical reference of the eight main concepts of personal branding (the eight laws of personal branding) is used. The data is collected through videos or descriptions published on the Tiktok account @vmuliana using a qualitative approach. This study concludes that Vina Muliana's personal branding through her Tiktok account (@vmuliana) fulfills all eight main concepts for personal branding, namely specialization, leadership, personality, difference, appearance, unity, constancy, and good name